Exotic criticality in the dimerized spin-1 $XXZ$ chain with single-ion anisotropy - Satoshi Ejima, Tomoki Yamaguchi, Fabian H. L. Essler, Florian Lange, Yukinori Ohta, Holger Fehske (SciPost Physics, 2018)
We consider the dimerized spin-1 $XXZ$ chain with single-ion anisotropy $D$. In absence of an explicit dimerization there are three phases: a large-$D$, an antiferromagnetically ordered and a Haldane phase. This phase structure persists up to a critical dimerization, above which the Haldane phase disappears. We show that for weak dimerization the phases are separated by Gaussian and Ising quantum phase transitions. One of the Ising transitions terminates in a critical point in the universality class of the dilute Ising model. We comment on the relevance of our results to experiments on quasi-one-dimensional anisotropic spin-1 quantum magnets.